Motif dan Makna Endorsement Bagi Pelaku Bisnis Produk Fashion Wanita - Arief, Annisa Gusridina; Triwardani, Ike Junita; Kurniadi, Oji (Jayapangus Press, 2024)
Digital-based marketing, especially through endorsement activities with influencers, has become a significant phenomenon in women's fashion online businesses. Businesses are competing to find innovations in promotion to increase their business. Endorsement, as a form of collaboration between businesses and influencers, plays an important role in achieving this goal. This research aims to explore and analyze the meaning and motives behind their decision to use endorsements. This research uses a a phenomenological approach to obtain a clear picture and information about the meaning and motives of endorsement by conducting in-depth interviews and observations to collect data from business people including Cekhas.id, Kirei Outfit, Deenay, Damakara, and Otashawl. The results showed that the meaning of endorsement is manifested in the formation of brand identity. The business actors interpreted the endorsement because of the experiences felt and experienced while doing endorsement activities for a long period of time. The endorsement motives are divided into two main categories, namely first,